How do Individuals Form Their Motivations to Expatriate? A Review and Future Research Agenda - Arifa, Y. N.; El Baroudi, S.; Khapova, S. N. (Frontiers in Sociology, 2021)
For two decades, individual motivations to expatriate have received substantial attention in the expatriation literature examining self-initiated and assigned expatriation. Recently, however, this literature has changed direction, demonstrating that prior to forming their actual motivations, individuals undergo a process wherein they actively form those motivations. No review has yet unraveled this motivation process, and this systematic literature review fills this gap. Using the Rubicon Action model that discusses the motivation process of expatriation, this article demonstrates that for self-initiated and assigned expatriation, individuals follow similar processes: expatriation expectations are formed; then, they are evaluated; and finally, preferences are built that result in motivations to expatriate. Findings for each stage are discussed in light of their contributions to the expatriation literature. For major gaps, new research suggestions are offered to advance our understanding of the individual motivation process that expats experience prior to forming their motivations to move abroad.